Ms. Determination of the operational capacity of the freezing tunnel of a fishing company - Olivares, Fabiola (2022)
This study determined the operational capacity of the freezing tunnel of a fishing services company. The operation of the equipment was inspected, the theoretical operational parameters were collected, and in 40 selected points, the speed (1,8 – 4,4 m/s) and temperature (–25 °C and –11 °C) of the air, and the initial and final freezing temperatures of whole gutted mahi-mahi (Coryphaena hippurus) were evaluated. The real operating capacity of the equipment (77,2 kW) was calculated by applying mathematical expressions that allowed to determine the thermal loads, and later it was compared with the design capacity (75 kW). The speed and temperature of the air inside the equipment and the temperature distribution of the product were not uniform. They depended on the location of the fans and the measurement points. These variations affected the thermal loads generated by the product and were directly proportional to the speed of the air and inversely proportional to the temperature in the center of the product. The results showed the tunnel was working above its capacity; freezing times were higher than those reported for mahi-mahi frozen at temperatures between –18 ºC and –20 ºC.